Factors Contributing to the Utilization of Adult Mental Health Services in Children and Adolescents Diagnosed with Hyperkinetic Disorder - Hilario Blasco-Fontecilla; Juan J. Carballo; Rebeca Garcia-Nieto; Jorge Lopez-Castroman; Analucia A. Alegria; Ignacio Basurte-Villamor; Juncal Sevilla-Vicente; Rocio Navarro-Jimenez; Teresa Legido-Gil; Consuelo Morant-Ginestar; Miguel Angel Jimenez-Arriero; Jeronimo Saiz-Ruiz; et al. (The Scientific World Journal)
Objectives. To examine whether age of First diagnosis, gender, psychiatric comorbidity, and treatment modalities (pharmacotherapy or psychotherapy) at Child and Adolescent Mental Health Services (CAMHS) moderate the risk of Adult Mental Health Services (AMHS) utilization in patients diagnosed with hyperkinetic disorder at CAMHS. Methods. Data were derived from the Madrid Psychiatric Cumulative Register Study. The target population comprised 32,183 patients who had 3 or more visits at CAMHS. Kaplan-Meier curves were used to assess survival data. A series of logistic regression analyses were performed to study the role of age of diagnosis, gender, psychiatric comorbidity, and treatment modalities. Results. 7.1% of patients presented with hyperkinetic disorder at CAMHS. Compared to preschool children, children and adolescents first diagnosed with hyperkinetic disorder at CAMHS were more likely to use AMHS. Female gender and comorbidity with affective disorders, schizophrenia, schizotypal and delusional disorders increased the risk of use of AMHS. Pharmacological or combined treatment of hyperkinetic disorder diagnosed at CAMHS was associated with increased risk of use at AMHS. Conclusions. Older age of first diagnosis, female gender, psychiatric comorbidity, and pharmacological treatment at CAMHS are markers of risk for the transition from CAMHS to AMHS in patients with hyperkinetic disorder diagnosed at CAMHS.